Exploring the personal experiences, barriers and expectations among caregivers and people with physical disabilities in a teaching hospital in Kuantan, Malaysia - Abdul Hadi, Said; Farah Natashah, Mohd; Mohamad Zairi, Baharom; Aznan, Md Aris; Mohamad Afiq, Mohamad Shahrin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Introduction: Improving healthcare services for people with physical disabilities (PWPD) is critical to health achievement worldwide. The caregivers of PWPD play a pivotal role in facilitating early diagnosis, participating in treatment decision-making, and selecting suitable service providers. Therefore, this study aims to explore the personal experiences, barriers, and expectations of PWPD and their caregivers in receiving healthcare services at a teaching hospital in Kuantan. Method: A total of 18 participants, including PWPD and their caregivers attending the hospital, were purposely selected to participate in individual in-depth interviews following a generic qualitative study design. These interviews were conducted in Malay using a topic guide, and the sessions were recorded, transcribed, and subsequently analyzed. The data analysis process followed a qualitative data analysis framework. Results: The findings of our analysis revealed that most participants expressed satisfaction and shared positive experiences with the healthcare services they received. They emphasized that improved facilities and high-quality equipment played a significant role in enhancing their satisfaction. However, several barriers were identified, primarily related to physical limitations. These barriers included insufficient parking availability, deteriorated wheelchair conditions, long distances between different areas, overcrowding in the pharmacy, heavy doors, the absence of automatic beds, excessively high emergency buttons, limited shopping options, and restricted operating hours. Participants also expressed expectations for improved transparency in doctor-patient communication and enhanced hospital promotions. Conclusion: To enhance future healthcare provision, it is essential to understand and address the expectations of PWPD and their caregivers at various levels within the healthcare system.